Lightning Protection of Aircraft, Power Systems and Houses Containing IT Network Electronics - Hoole, P.R.P; Sharip, M.R.M.; Fisher, J.; Pirapaharan, K.; Hj Othman, Al Khalid; Julai, Norhuzaimin; Anak Rufus, Shirley; Sahrani, Shafrida; Hoole, S.R.H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Over the past decade, there has been an increasing interest in lightning and lightning protection for several reasons, including the proliferation of microelectronic equipment and IT systems in mission-critical systems as well as in everyday use in banks to homes. Lightning strikes to power lines produce large fast transient voltage and current surges which trickle down to IT systems, military command and control systems as well as to several other microelectronic equipment and control systems. Moreover, aircraft are struck by lightning when it is parked on ground, landing and taking off or in military operations where the aircraft has to keep close to the ground even when the atmosphere is electrified by thunderclouds. In this paper, we explore the protection of electronic equipment, structures and in-house systems from lightning. The paper will also explore lightning related Electrostatic Discharge (ESD) threat to aerospace vehicles and microelectronic systems. This is especially so with the increased use of non-metallic, composite material for the aircraft body. Moreover, the paper will report on the important lightning techniques used in the protection of electric power systems and houses.